PENGGUNAAN MEDIA WAYANG FANTASI DALAM MENGEMBANGKAN KEMAMPUAN BAHASA ANAK USIA DINI - Nadiyah; Fitriah; Mastikawati; Rina (LP2M IAIN Sultan Amai Gorontalo, 2025)
This research aims to develop the language skills of children aged 4-5 years through the use of fantasy puppet media in Al-Fajri Early Childhood Education (PAUD), East Tanjung Jabung. This Classroom Action Research (PTK) was carried out in two cycles, each consisting of planning, implementation, observation and reflection. The data collected includes children's ability to retell fairy tales and name the puppets. The results showed significant improvements in both abilities. At the end of Cycle II, 75% of children reached the BSB category in retelling fairy tales, and 83% of children reached the BSB category in naming puppets. These findings indicate that fantasy puppet media is effective in improving children's language skills through interactive and fun learning. This research supports the theories of constructivism and multiple intelligences, and provides an important contribution to the development of creative learning media based on local culture. The conclusion of this study shows that the use of fantasy puppet media is effective in improving the language skills of early childhood. Therefore, it is recommended that teachers and parents be more active in using creative media such as puppets to support children's language development, so that they can communicate better and build the social skills needed in everyday life